Educative television during COVID-19 pandemic in Spain - Collado-Alonso, Rocío; García-Matilla, Agustín; de Andrés-del Campo, Susana; Merchán Bermejo>, José Mª (Quórum Académico, 2022)
In the context of the Covid-19 pandemic, educational broadcasting for children and adolescents returned to the headlines to show the huge gaps that exist in the apparently developed world. In a few days, the Spanish public television put together a series of educational contents, in an effort to make up for school closures and support students from low-income households – 300 broadcast hours in two time slots and for two public television stations, La 2 and Clan. The research includes an overview of educational television, an assessment of its relevance today, a review of the educational contents put together by the Spanish public television service and the Ministry of Education, and a discussion of the criticisms advanced by education associations and ordinary citizens, followed by a diagnosis of the situation